Intellectual Property Rights and the TRIPS Agreement : An Overview of Ethical Problems and Some Proposed Solutions - Sonderholm, Jorn (2012)
The Agreement on Trade-Related Aspects of Intellectual Property Rights negotiated in 1986 under the auspices of the General Agreement on Tariffs and Trade, the institutional predecessor of the World Trade Organization, incorporated substantial and uniform protections of intellectual property rights into the international trade system. A large body of contemporary academic literature suggests that intellectual property rights on socially valuable goods such as essential medicines give rise to a number of ethical problems. This review paper seeks to give an overview of these problems. Moreover, it offers an outline and discussion of a number of proposals as to how these problems might be alleviated. The paper is primarily descriptive in character. This means that although a personal perspective is sometimes offered, the primary ambition of the paper is not to argue for, and defend, a particular solution to the issues discussed. The aim is rather to highlight, explain and put into perspective a number of important arguments in the debate on the ethical nature of intellectual property rights so that policy-makers and other stakeholders are relatively well-equipped to make up their own mind on the issue.